2005
DOI: 10.1111/j.1365-294x.2005.02594.x
|View full text |Cite
|
Sign up to set email alerts
|

The mtDNA catalogue of all Portuguese autochthonous goat (Capra hircus) breeds: high diversity of female lineages at the western fringe of European distribution

Abstract: Goat is believed to be the first true livestock domesticated and, apart from its historical importance, keeps playing an essential economic role in very diverse human societies. We have analysed the female gene pool of all Portuguese autochthonous breeds (Bravia, Serrana, Charnequeira, Serpentina and Algarvia) through the mtDNA HVI sequencing of 288 unrelated animals sampled throughout the country. All breeds proved to be extremely diverse (average haplotype diversity of 0.977), in contrast with the Portuguese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 27 publications
6
46
1
1
Order By: Relevance
“…This difference, i.e., the low variability, could be explained by founder effects, low effective population size, and/or the short evolutionary time elapsed compared to native Portuguese herds. In addition, Pereira et al (2005) found two events of insertion and two deletions, in contrast to our results, where no indels were observed. The Crespa nucleotide diversity (π = 0.0075) was high compared to that of the other breeds reared in the same region, and Crespa had the highest number of shared haplotypes, with Anglo-Nubian, Boer, and Saanen in the same haplotype (Figure 3).…”
Section: Crespa As a Distinct Genetic Clustercontrasting
confidence: 56%
See 2 more Smart Citations
“…This difference, i.e., the low variability, could be explained by founder effects, low effective population size, and/or the short evolutionary time elapsed compared to native Portuguese herds. In addition, Pereira et al (2005) found two events of insertion and two deletions, in contrast to our results, where no indels were observed. The Crespa nucleotide diversity (π = 0.0075) was high compared to that of the other breeds reared in the same region, and Crespa had the highest number of shared haplotypes, with Anglo-Nubian, Boer, and Saanen in the same haplotype (Figure 3).…”
Section: Crespa As a Distinct Genetic Clustercontrasting
confidence: 56%
“…Over the last few years, considerable effort has been devoted to characterizing the genetic diversity of African, Asian, and European goats (e.g., Azor et al, 2005;Pereira et al, 2005;Cañón et al, 2006;Naderi et al, 2007;Çinar Kul and Ertuğrul, 2011), but locally adapted Latin American breeds have received much less attention. In Brazil, a few studies have recently addressed the existence of local breeds using either microsatellites or mtDNA, and all have focused on those from the northern region of the country, for example the Canindé, Graúna, Marota, Moxotó, Repartida, and Serrana Azul (Araújo et al, 2006;Menezes et al, 2006;Oliveira et al, 2007Oliveira et al, , 2010.…”
Section: Crespa As a Distinct Genetic Clustermentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that the population is descended from numerous introductions between the 1840s and 1920s from at least four mainland populations across the UK (Marshall, 1998), and that red deer have been the subject of extensive human translocation throughout the UK and Europe for many centuries (Whitehead, 1964;Hartl et al, 2003;Long, 2003), the high levels of divergence between mtDNA haplotypes on Rum are not surprising. Similar patterns of mitochondrial divergence within restricted geographic ranges have been observed in both this species (Feulner et al, 2004), and within breeds of domestic species (Guiffra et al, 2000;Pereira et al, 2005). Furthermore, there is good reason to expect similar levels of divergent matrilineal ancestry in other Scottish populations of red deer: records show regular introductions from populations in English parks across the mainland and islands throughout the last three centuries (Whitehead, 1964).…”
Section: Discussionmentioning
confidence: 63%
“…To date, the effects of human management practices on the population genetics of vertebrate game species have received little attention, despite their potential economic and conservation implications. The regular practice of human translocation of individuals between populations, often geographically distant from one another, in both domestic and game species can act to enhance genetic differentiation between populations, while also blurring a species' phylogeographic structure and undermining expected patterns of isolation by distance (Guiffra et al, 2000;Pereira et al, 2005). At the same time, selective culling to maximise some phenotypic quality (eg antler or horn size in males) is likely to alter levels of genetic variation or specific allele frequencies associated with these traits (Harris et al, 2002;Coltman et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%